Chapter 14 Developing new approaches, stepping beyond categories Transnationalism and youth mobility trajectories in migration research - Mazzucato, Valentina (Taylor & Francis, 2024)
Is it possible or even desirable for scholars to try to extricate the personal and subjective from their research agenda? Might something be lost from research in pursuit of 'objectivity'? If objectivity is so important, why do many scholars study something that is dear or familiar to them? This book acknowledges the ways in which personal experience affects research and how the process of doing research sheds light on personal histories. Offering a collection of multi-layered reflections on the importance that the connection between biography and research can hold for developing meaningful knowledge and new methodologies, it considers the influence of scholars' experiences of migration on their careers. With attention to the ways in which personal biographies have been instrumental in developing the research and methodological sensitivity of accomplished migration scholars across a variety of disciplines, it sheds light on the importance of reflexivity and subjectivity as assets in research rather than obstacles. Positioning the researchers' experiences at the centre of the process of enquiry, Migrant Scholars Researching Migration will appeal not only to scholars of migration and diaspora studies, but to those with interests in research methodology and biographical research.